Pengaruh Pemberian Stretching Lower Extrimity Dan Core Stability Terhadap Keseimbangan Dinamis Pemain Basket Ukm Ums - Wijianto Wijianto; Suci Indah Ramadhani (Prosiding University Research Colloquium, 2022)
Components of physical conditions namely speed, strength, endurance, flexibility, strength, coordination, balance, and agility in improving basketball player performance. one of them is the relationship between ability to balance and the risk of sports injury has been determined in many cases, but the relationship between ability and balance between athletics is less clear. There is limited data on skills training in elite athletic motor training. Training on the balance between endurance training, this finding endurance training produces superior results for high jump and run time. The importance of balance for the basketball player itself reduces injury and improves performance during matches. Determine the effect of giving low stretches and core stability on dynamic equilibrium. paired test results t sample test in the consent group obtained an average result in pair 1 namely 2.35824 with a significant value of 0.000 where p <0.05 then Ha was accepted and pair 2 was 1.67059 with a significance value of 0.005 while the value of p <0.05 then Ha can be accepted which stretches the lower extrimity and core stability needed to increase dynamic balance. Supporting the stretching of lower severity and core stability can improve the dynamic balance of the basket player.